Does Globalization Endanger the Social Market Economy? (Economic and Political Thought, 2010)
Globalization is a real threat for the social market economy and globalizationdoes not protect weak, ill and helpless people. Multinational corporationsacknowledge only one criterion, i.e. profit. To illustrate the situation theauthor presents a short characteristic of international economic co-operation.He asks the following questions: What was the aim of deregulation of theeconomic markets? What chaos was caused by that deregulation? How canthese negative tendencies be reversed?In conclusion the author speaks about the negative influence of globalizationon the social market economy. He also describes the features ofthree attitudes towards globalization, i.e. a radical one, a neoliberal one anda reformist one. Globalization in its present version is spontaneous and willhave to be “civilized” in the forthcoming decade.